Konstytucyjne podstawy wolności religijnej w wybranych państwach Europy i Ameryki Łacińskiej - Osuchowska, Marta; Syryt, Aleksandra (Polski Przegląd Stosunków Międzynarodowych, 2018)
The constitutional basis for religious freedom in selected countries in Europe and Latin America Religion helps man keep his own identity. It enables him to participate in a common heritage. The study provides the constitutional basis for religious freedom in the individual dimension in selected countries in Europe and Latin America. The authors discuss the provisions on religious freedom enshrined in the constitutions of Italy, Spain and Portugal, as well as Argentina, Chile and Colombia. The analysis leads to the conclusion that religious freedom is a human right protected both in the constitutions of European countries as well as in the constitutions of Latin American countries. The inclusion of the provisions on religious freedom in the individual dimension in the constitutions is due to certain similarities of the system of European and Latin American. Common features of both systems is that Europe and Latin America belong to the so-called Western civilization. The legal systems of Latin American countries formed primarily on the basis of Roman law. Although the wording of the provisions on religious freedom in the individual dimension in the constitutions of Latin American countries is similar to the editorial rules of the constitution states of Europe, in practice there are other ways to implement this freedom and guarantees its protection.